De l’usage de l’intertexte biblique dans quelques poèmes de George Herbert et de John Donne - Jean-Louis Breteau (Revue LISA)
Controversial as the underlying theology of metaphysical poetry may be, such poets as George Herbert and John Donne extensively resorted to the use of the biblical intertext, and they had a thorough knowlege of both the hermeneutics and the poetics of their time. As a matter of fact, they cared more about conforming to the Word than to their Church’s rites and forms. And yet they did not read Scripture literally, but, like their contemporaries, freely indulged in the practice of typology, while displaying a great mastery of such poetic devices as emblems or conceits. Some differences can nevertheless be identified between Herbert’s and Donne’s respective approaches to religious poetry. In this study, a few poems are closely examined. “Easter Wings” and “Prayer I” can be seen to exemplify Herbert’s so-called “plain”, but in fact very elaborate, writing, while “Good Friday” and “At the round earth’s imagined corners” illustrate Donne’s paradoxical and ironical ways.